PEMANFAATAN “WHATSAPP” SEBAGAI MEDIA KOMUNIKASI DOSEN DENGAN MAHASISWA BIMBINGAN SKRIPSI (Studi Analisis Deskriptif Pada Mahasiswa Ilmu Komunikasi Bimbingan Skripsi Universitas Dehasen Bengkulu Tahun 2016 ) - Sri Narti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2017)
This study, entitled The Use of Whatsapp asa CommunicationMedia for studentsthesis guidance. This study aimed to describe the use of whatsapp as a media of communication betweenlecturers with students for thesis guidance. Therefore, it is interesting to examine how students communicate to the supervisor via whatsapp, includingthe consultations about the thesis guidance in performing routine tasks for the students’ final thesis. The subjects were students of communication department who were doing thesis guidance numbered 72 people in 2016. The informants werethe lecturersof 10 peoplewho certainly connected with the researcher’s whatsapp. The researcher used the theory of diffusion of innovation and social penetration theory to analyze the data. While the method used in this research was a field study where the researcher plunged into the field and the data were taken directly from the study sites. Furthermore, the researcherstudied literatures by finding material from books, articles, and scientific journals. With the phenomenological method, the researcher obtained an overview of the entire process experience of using whatsapp as a communication between the lecturers with the students. Through whatsapp interpersonal communication activities will be established as an alternative media when students and lecturers could not hold a thesis counseling process face to face. They will continue discussing without space and time. This is in order to anticipate a very shortthesis guidance schedule and lecturers’ bustle. Students are assisted without waiting to hear from lecturers about guidance schedules, thesis discussion and others. Because the whatsapp discussion group has been formed by lecturers and students for thesis guidance. This is in order to motivate the students, improve academic activities such as paper consultation, and avoid students from stress feeling during thesis guidance. Keywords: Whatsapp, Communication Media, Interpersonal Communication, Lecturers and Students.